The Influence of Organizational Culture, Leadership Style, Quality of Human Resources, and Work Motivation on Employee Performance - MA Faishol Zuhri; Musa Hubeis; Nurhasanah Nurhasanah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
The performance report data gathered from Key Performance Indicators, Bureau of Budget Planning and International Cooperation, Ministry of Public Works, and Public Housing of the Republic of Indonesia 2015-2020 shows they did not reach their target because of factors such as organizational culture, leadership, the quality of human resources, and working motivation. Therefore, this study aims to analyze both partial and simultaneous impacts of organizational culture, leadership, the quality of human resources, and workingmotivation on employee performance in the Bureau of Budget Planning and International Cooperation, the Ministry of Public Works, and Public Housing of the Republic of Indonesia. One hundred staff members were involved as the samples of the study. We collected data by using a questionnaire